Otoacoustic Emission Findings in Rett Syndrome - Nicholas, Sarah; Kei, Joseph; Woodyatt, Gail; McPherson, Bradley (Journal of the American Academy of Audiology, 1999)
Rett syndrome is a neurologic disorder affecting mainly females after a seemingly normal 6 to 18 months of life. The resulting developmental disabilities include apparent dementia and loss of acquired language, social skills, and purposeful hand use. The present investigation assessed 10 individuals with Rett syndrome and a control group matched for age and sex. The present study aimed to determine the clinical feasibility of obtaining otoacoustic emissions (OAEs) from the Rett syndrome group and to compare the characteristics of the transient evoked and distortion-product OAEs obtained from the two subject groups. Results indicated that OAE evaluation is a clinically feasible method of assessing individuals with Rett syndrome. The Rett syndrome group had less robust OAEs, especially in the higher frequencies, when compared to the control group. Seven of the Rett syndrome group were identified as having reduced or absent OAEs in at least one ear. These findings suggest a need for hearing screening at an early age and monitoring of hearing on a regular basis.Abbreviations: ABR = auditory brainstem response, DPOAEs = distortion-product otoacoustic emissions, LVR = late vertex response, MLR = middle latency response, OAE = otoacoustic emission, SNR = signal-to-noise ratio, TEOAEs = transient evoked otoacoustic emissions, VRA = visual reinforcement audiometry, WWR = whole-wave reproducibility
Keywords: Hearing impairment; otoacoustic emissions; Rett syndrome